PENGARUH FAKTOR KULTUR ORGANISASI, MANAJEMEN, STRATEGI, KEUANGAN, AUDITOR DAN PEMERINTAHAN TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Eka Fransiska Firdaus; Erni Suryandari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2008)
Accounting fraud, where the financial reports are reported not in compliance with the generally accepted accounting principles can undermines the credibility of the financial reporting system. Indeed the effects of accounting fraud can be devastating for investors. The objectives of the research is to explain the effect of organization culture, managerial, strategic, financial ratios, auditor factors and governance factors to the tendency of accounting fraud. The research population was 805 companies listed in the Indonesian Stock Exchange (IDX). The research samples were 125 public companies consisting 12 fraud firms and 113 non- fraud firms. Binary logistic regression was used to test the hypothesis. The results showed that number of related party transactions, firm size, and auditor's unqualified opinion affected the tendency of accounting fraud significantly. Current asset composition in total asset, capital turnover, aquitition, financial leverage, CEO age, CEO MBA, KAP, professional accountant and good corporate governance, These results advance the understanding of accounting fraud.